Multidisciplinary nursing care in chronic Chagas disease: a scoping review - Silva, Ângelo Antônio Oliveira (2025)
This research was funded by the Coordination for the Improvement of Higher Education Personnel in Brazil (CAPES; Finance Code 001, 88887.805768/2023-00, 88887.637641/2021-00, 88887.805717/2023-00, 88887.637758/2021-00, and 88887.637869/2021-00) and the Research Support Foundation of the State of Bahia (FAPESB; BOL0543/2020). FLNS is research grantee of the National Council for Scientifc and Technological Development-Brazil (CNPq; processes no. 306448/2023-8). The funders had no infuence on the study design, data collection and analysis, decision to publish, or preparation of the manuscript.